2012
DOI: 10.1007/s12253-011-9489-1
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-To-Mesenchymal Transition Induced by Freund’s Adjuvant Treatment in Rat Mesothelial Cells: A Morphological and Immunocytochemical Study

Abstract: Intraperitoneal injection of Freund's adjuvant induces acute peritonitis. By the time of the Freund's adjuvant treatment the flat, simple squamous epithelial cells became rounded, cuboidal shaped, many of them have lost their connection with the neighbouring cells and detached from the basement membrane. The macrophage markers' (ED1, OX43 and CD68) expression also increased in the mesothelial cells and more mesothelin and anti-ED1 double-labelled cells were found freely present close to the surface. The cytoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…1). Keratin and vimentin are commonly used markers for identifying mesothelial cells (16,17). Keratin and vimentin were predominantly localized in the cytoplasm, which is consistent with the characteristics of mesothelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…1). Keratin and vimentin are commonly used markers for identifying mesothelial cells (16,17). Keratin and vimentin were predominantly localized in the cytoplasm, which is consistent with the characteristics of mesothelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous light microscopical data revealed that mesothelial cells lose their epithelial character (decreased cytokeratin, E-cadherin expression) upon Freund's adjuvant treatment and obtain a mesenchymal phenotype by expressing vimentin [26] . The inflammatory stimuli changed remarkably the ultrastructure of mesothelial cells as well.…”
Section: Resultsmentioning
confidence: 95%
“…In a previous paper we have shown that rat mesenteric mesothelial cells undergo EMT upon inflammatory stimuli induced by Freund's adjuvant treatment [26] . In the present paper we furnish additional evidence for the inflammatory response of the tissue by showing that the morphological changes at the ultrastructural level were in correlation with the expression levels of pro-inflammatory cytokines (IL 1α, 1β and IL-6) measured in mesothelial cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…DURING INFLAMMATION INDUCED EMT During inflammation-induced EMT mesenteric mesothelial cells start to express macrophage markers (OX43, ED1) as well [12,52], suggesting that they might be transformed into macrophage-like cells [53]. Our previous data showed that under inflammatory stimuli the number of peritoneal macrophages dramatically increased [54].…”
Section: Mesothelial Cell-macrophage Transition (Mmt)mentioning
confidence: 99%